2021
DOI: 10.1021/acs.inorgchem.1c03049
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Trinuclear Copper(I) Complex Exhibiting Aggregation-Induced Emission: A Novel Fluorescent Probe for the Selective Detection of Gold(III) Ions

Abstract: Coordination complexes with aggregation-induced-emission (AIE) behavior has drawn much attention because of their promising applications. Conventionally, the AIE-active metal–organic complexes are prepared from an AIE-active organic ligand, and the construction of such coordination complexes from aggregation-caused-quenching (ACQ) ligands is still challenging. Herein, we have synthesized two new cyclic trinuclear complexes (CTCs), namely, 1 and 2, from copper­(I) and silver­(I) and a ACQ ligand [4-(3,5-dimethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…34). Such PL quenching might be attributed to the strong metal-metal interactions between Au(III) and Ag(I)-CTUs in the frameworks, resulting in enhancement of radiative decay 28 . To further prove this hypothesis, we prepared a COF, TFPT-BTAN (see the SI) 33 as a reference with similar pore size and nitrile groups but without Ag(I)-CTUs.…”
Section: Pl Properties and Detection Of Au 3+ Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…34). Such PL quenching might be attributed to the strong metal-metal interactions between Au(III) and Ag(I)-CTUs in the frameworks, resulting in enhancement of radiative decay 28 . To further prove this hypothesis, we prepared a COF, TFPT-BTAN (see the SI) 33 as a reference with similar pore size and nitrile groups but without Ag(I)-CTUs.…”
Section: Pl Properties and Detection Of Au 3+ Ionsmentioning
confidence: 99%
“…Although a few MOFs have been demonstrated with the capability of gold adsorption, to our best of knowledge, MOFs that can concentrate ultra-trace gold (<20 ppb) from complex liquid have rarely reported so far (See Supplementary Table 12) [21][22][23][24][25][26][27] . Recently, we found that a Ag(I) cyclic trinuclear unit (CTU) can be used for rapid and selective sensing of Au(III) ion with a low limit of detection (LOD) of 650 ppb via strong metallophilic attractions 28 . We hypothesize that the incorporation of Ag(I)-CTU into MOFs may be a promising strategy for improving the affinity of MOFs toward gold.…”
mentioning
confidence: 99%
“…In our previous studies, we found that the modification of the pyrazole ligand significantly altered the PL properties of Cu-CTCs. 20,36 Boron dipyrromethene (BODIPY) is an organic dye with excellent PL properties including strong visible light adsorption, high photo-stability, and high quantum efficiency. [37][38][39][40] Thus, we envisioned that the incorporation of the BODIPY motif in Cu-CTCs may address the above-mentioned issues and hopefully become the first example of a Cu-CTC-based PS.…”
Section: Introductionmentioning
confidence: 99%
“…These functional hybrids are usually equipped with permanent porosities and present distinct physicochemical properties in sorption, separation, catalysis, photoluminescence, magnetism, and so on. In the process of acquisition of desirable MOFs, many external factors have a great influence on the regulation of diverse architectures, among which the utilization of organic linkers could be considered as the most important one. Especially, the N-donor molecules, exemplified by the pyridine and azole derivatives, are largely employed to assist the construction of promising MOFs by virtue of their merits in satisfactory coordination geometry and abilities. According to the hard and soft (Lewis) acid and base theory, the “soft” N atom has a high affinity to the “soft” cation like Cu + , thus giving rise to a large number of robust Cu­(I)-based MOFs with outstanding physical performance. The works on Cu­(I) cyclic trinuclear complexes (CTCs) are representative of such compounds. The combination of closed-shell coinage metal with angular ditopic anionic linkers such as pyrazolate and 1,2,4-triazolate has afforded a series of trinuclear metallocycles with M–M interactions featuring excellent photoluminescence behaviors. In addition, the assembly of copper-based porous networks for selective guest sorption is a trend in terms of seeking new adsorbents and separators.…”
Section: Introductionmentioning
confidence: 99%